Respuesta :

We need to solve for the x in the equations given.
(7x+4)/5 + (4x-2)/2=27
[(7x+4)*2 + (4x-2)*5]/ 10 = 27
(14x+8+20x-10)/10 = 27
(14x+8+20x-10) = 270
34x = 272
x = 8
---------------------

(8x+7)/6 + (9x-2)/2=6
[(8x+7) + (9x-2)*3] / 6 = 6
(8x + 7 + 27x - 6) / 6 = 6
(8x + 7 + 27x - 6) = 36
35x = 35
x = 1
----------------------------

2/(x-4) + 8/(2x-8)=13
[(2*2) + 8] / (2x-4) = 13
12 / (2x-4) = 13
13(2x-4) = 12
26x - 52 = 12
26x = 64
x = 64/26
x = 32 / 13 
-----------------------------------

2/(x+5) - 4/(7x+35)
[(2*7) - 4] / (7x+35)
(14-4)/(7x+35)
10 / (7x+35)